Financial Performance Analysis by Using Financial Ratios at CRRC. Co., Ltd in China - Fang Ziling (Oikonomia: Jurnal Manajemen, 2023)
Purpose This  research is aimed at analyzing in this paper is financial performance by using financial ratios at PT.  CRRC.  CO., LTD in China.  Methodology The analytical method used 4 main factors, namely liquidity, solvability, activity, profitasbilitas.  Findings The results showed that liquidity capacity had been increased, the company's financial liabilities returning loans were also smaller and the speed of total asset turnover was accelerated, even though the ability of profitability had increased but other expenses of the company were many. The company's financial condition is quite stable and promising. But still have to be careful with the position in the market compared to its competitors. Suggestion The company must ensure its future strategy in facing competition and strengthening its position in the market.